The effect of special preparation exercises (cardio) on some forms of strength for the arm muscles for bodybuilding players in the Classic Physique class - Abdel – Saheb , Ahmed; Abdel Hassan , Ghassan (Journal of Physical Education, 2025)
Bodybuilding is a sport that relies on exercises with varying intensity and training loads in order to gain strength and large muscle masses. The external appearance has a special evaluation that we seek to reach through physical training that achieves high physical coordination because it is the key to rising to the first ranks in competitions. From this, the concept of modern training has led to the discovery of many new training methods, techniques and exercises, which have been applied to most sports and have obtained results that should be paid attention to. Among these exercises are modern cardio exercises, which work to develop the circulatory functional systems (cardiac and respiratory systems) and raise endurance physical fitness. It also significantly helps to get rid of excess weight by reducing the amount of body fat for bodybuilding athletes in particular and for other sports in general. “This type of exercise can be adopted continuously to be an incentive to raise the athletic level. (Faisal, Bahaa Dhiab, 2019) The most difficult period faced by a bodybuilding athlete is the special preparation period because the athlete is under the influence of relatively high-repetition exercises with submaximal intensity and is subject to a strict, precise, and specific diet. This is what is applicable in the traditional methods of bodybuilding, and in contrast to these followed methods, other, updated methods have emerged. It is one of the cardio exercises that helps bodybuilders face the difficulty of the special preparation period, as it may have an impact on the level of achieving prominence and muscle definition of the player in a healthy and sound manner while saving time. The research aims to prepare exercises for the special preparation stage of bodybuilding in the cardio style for the players of the Classic Physique category and to identify the effect of the exercises of the special preparation stage for body building in the cardio style on some forms of strength of the arm muscles for the bodybuilding players of the Classic Physique category. The hypothesis of the research was that there is a positive effect. For exercises in the special preparation phase for body building in the cardio style between pre- and post-tests, and for the benefit of post-tests in some forms of strength for the arm muscles for body-building players in the Classic Physique category. The researchers used the experimental method by designing an equal experimental group with two pre- and post-tests. The researchers chose a random sample consisting of (14) bodybuilding players in the Classic Physique category from the participants in the recent Iraqi championship. Their heights ranged between (171 cm - 175 cm) and their weights (77-83) and who They represent (35%) of the research population of (40) players in Baghdad. The homogeneity of the research sample was calculated in terms of age, weight, height, and training age, as shown in Table (3), and the value of the skewness factor (+1) was extracted to indicate the homogeneity of the research sample. The results of the research were positive through the results of post-tests of cardio exercises, and the researchers recommended using cardio exercises for bodybuilding athletes in the Classic Physique category during the special preparation period instead of traditional exercises.